2012
DOI: 10.4236/fns.2012.35094
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Quality of Chicken Sold in Accra and Determination of D<sub>10</sub>-Value of <i>E. coli</i>

Abstract: Chicken is an excellent source of good quality protein, but it is highly susceptible to microbial contamination and often implicated in food borne disease. The microbiological quality of chicken at different retail outlets (supermarkets, local markets and farms) in Accra was investigated, and D 10 -values of E. coli in refrigerated and frozen retailed chicken was determined. The microbiological quality of chicken was studied by analyzing 27 chicken thigh samples collected from the retail outlets. D 10 -value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 20 publications
5
38
2
2
Order By: Relevance
“…The result of this study was much lower than presence of fecal coliforms in meat and meat studied by many researchers [41,42]. Other study results have also been reported for retail chicken (50% incidence of E. coli) in Australia [43] which was much higher than the present study.…”
Section: Discussioncontrasting
confidence: 55%
“…The result of this study was much lower than presence of fecal coliforms in meat and meat studied by many researchers [41,42]. Other study results have also been reported for retail chicken (50% incidence of E. coli) in Australia [43] which was much higher than the present study.…”
Section: Discussioncontrasting
confidence: 55%
“…This exposed the consumers to a risk of eating poultry products that are contaminated with coliforms (Cardinale et al, 2005). The presence of E. coli in chicken samples is an indication of faecal contamination probably at one stage of preparation or from the materials used (Adu-Gyamfi et al, 2012). Handling food with unwashed hands may result in cross-contamination, hence leading to introduction of microbes on safe food (CAC, 1997).…”
Section: Roasted Chicken Samplesmentioning
confidence: 99%
“…; Adu‐Gyamfi et al . ). These products are considered to be well‐done by the consumer because of their baked appearance; however, they certainly have to be effectively heated before consuming (MacDougall et al .…”
Section: Introductionmentioning
confidence: 97%